The Functional Relationship of Education with Economic, Philosophy and Political Philosophy - Deak, Victor; Tanama, Yulia Jayanti (International Journal of Social and Management Studies, 2021)
The main purpose of providing education is to humanize humans. Education is done so that people who learn can understand and understand and what has been learned can be useful for themselves and many people. Of course in practice education cannot run alone without dependence on other dimensions such as economics, philosophy, politics, and religion. All of that is automatically assembled for a more comprehensive education organization. This study uses descriptive qualitative research methods to be able to provide a real picture of the functional relationship of education with other dimensions through a study of educational literature, philosophy, politics, economics, and religion. The research is expected to make a real contribution to knowing the relationship between education and other dimensions. This research provides a clear picture for policymakers and education practitioners on how to build a new paradigm or perspective in the management of education in Indonesia.